Variación morfométrica de los renacuajos de la especie Leptodactylus lithonaetes como respuesta al nivel de agua de las charcas (2021)
The variation and heterogeneity of environmental factors in the ecosystem can be an important source for the variation and phenotypic plasticity of organisms. Tadpoles are model organisms for studying morphological variation shaped by the environment. In environments with fluctuating conditions, such as the ponds of the rocky outcrops of the Colombian Orinoquía, understanding how environmental factors may be influencing the morphological variation of tadpoles could provide information on this phenomenon and on the susceptibility of these individuals to fluctuating conditions even more drastic that are anticipated in the future. The main objective of the present study is to evaluate the morphometric variation of the tadpoles of Leptodactylus lithonaetes under different treatments of water level of ponds. Eggs of this species were collected in the Bojonawi Natural Reserve, Vichada (Colombia), and the tadpoles that hatched were divided into three water treatments (stable water, low water and desiccated water). The morphological variation...